Wireless distance charger / Izzuddin Sapiai & Amira Nur Syahidah Abdul Halim - Sapiai, Izzuddin; Abdul Halim, Amira Nur Syahidah (2015)
Nowadays, we live in a world where power is transmitted to our homes and electrical outlets using AC, then converted into DC for use in most of our electronic devices. Most of our smartphones and tablets are charged through micro-USB cables that are either connected to computers or to "wall-warts" which convert the electricity from AC to DC for us. It was not always that way. Not that long ago, it seemed like every manufacturer had a different connector to get the direct current into our devices. However, some tablets are still suffering from this illness, but we would not point any fingers to the culprits. Now we are looking at what could be the widespread adoption of "wireless charges" as a standard. Some of us think wireless charging will become commonplace and could end up inside speaker and other docks to recharge our devices while listening to music or watching movies. It will probably even end up in our cars. The wireless distance charger is committed to standardizing technology so that operation will be always possible. Yet, to ensure a wide and receptive market for wireless power transmission, this wireless distance charger is also focused on building a user oriented wireless charging experience. So, everyone will be able to charge anywhere